Determinants of saving behavior among generation Y students in Universiti Utara Malaysia - Noor Zaihan, Daud (2016)
Financial complexity is due to lack of financial knowledge, overspending on unnecessary items or due to impulse buying, and maintaining affluent lifestyles that prompted one's to resort to lending to satisfy their needs. Nowadays, Malaysian young adults are reportedly the main group trapped into debt problems. This study aims to investigate whether the independent variables (IV) e.g. financial literacy (FL), parental socialization (PS), peer influence (PI) and self-control (SC) have significant influence on the dependent variable (DV) which is saving behavior (SB) by applying the Theory of Planned Behavior (TPB). Four hundred and fifty (450) questionnaires were distributed to Malaysian Generation Y students in Universiti Utara Malaysia (UUM). The hypothesis for this study is tested using multiple regression analysis to determine the influence of financial literacy, parental socialization, peer influence, and selfcontrol towards saving behavior. The standardized coefficient beta (ß) for financial literacy is ß=0.316, p<0.05, this means that the results are found positively and significant since the significant value is below the confidence level of 0.05. The standardized coefficient beta (ß) for parental socialization is ß=0.261, p<0.05, peer influence is ß=0.002, p>0.05 and self-control ß=0.143, p<0.05. This means that both parental socialization and self-control are positive and significantly influence saving behavior. However, standardized coefficient beta (ß) for peer influence is ß=0.002, p>0.05, this means that the results is found to be insignificant since the significant value is above 0.05. Thus, this does not support the hypothesis three (H3) that states, "There is a significant relationship between peer influence and saving behavior among UUM Malaysian Generation Y". The study makes a significant contribution to assist educators to develop appropriate programs and financial advisors design relevant financial courses to help respondents in managing money and avoid the debt tracks.